2012
DOI: 10.1016/j.jff.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization and immunomodulatory activity of polysaccharides from the stem of Dendrobium officinale (Tiepishihu) in vitro

Abstract: Polysaccharide CharacterizationImmunomodulatory activity A B S T R A C TThe crude polysaccharide from the stem of Dendrobium officinale (DOP) was obtained by water extraction and ethanol precipitation. Two fractions of DOP, DOP-1 and DOP-2, were fractioned by DEAE cellulose and Sephacryl S-400 gel filtration column chromatography.Their molecular weights and monosaccharide compositions were studied. The immunomodulatory activity of DOP, DOP-1 and DOP-2 was evaluated with in vitro cell models.The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
4
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 31 publications
(30 reference statements)
12
80
4
2
Order By: Relevance
“…The molecular weights of polysaccharide were determined by the method described in previous research [15]. A high performance size elusion chromatography coupled with multi angle laser light scattering and refractive index (HPSEC-MALLS-RID) system was used.…”
Section: Molecular Weight Determinationmentioning
confidence: 99%
“…The molecular weights of polysaccharide were determined by the method described in previous research [15]. A high performance size elusion chromatography coupled with multi angle laser light scattering and refractive index (HPSEC-MALLS-RID) system was used.…”
Section: Molecular Weight Determinationmentioning
confidence: 99%
“…The polysaccharide of Juniperus scopolorum showed potent immunostimulant effect, via increase of NO production and release of proinflammatory cytokines by macrophages (IL-1, IL-6, TNF-α) (Schepetkin et al, 2005). In addition, the polysaccharide obtained from Dendobrium officinal raised macrophage levels of TNF-α, IL-1β (He et al, 2016) and NO production (Xia et al, 2012). Based on these, we believe that EP-Mt might stimulate leukocytes to release chemotactic substances, being considered a promisor candidate to be used in immunostimulant therapies.…”
Section: Resultsmentioning
confidence: 99%
“…The content and quality of DDP are considered to the key indicators for evaluating the quality of Dendrobium officinale (Jin et al, 2016). DDP is the multi-hydroxyl polymer composed of glucose, mannose, galactose, glucose acid, glucose acid, xylose, Arabia sugar, galactose acid and other monosaccharide (Xia et al, 2012). This study observed the effect of DDP on the adipogenic differentiation of BMSCs.…”
Section: Discussionmentioning
confidence: 98%